"THE GILDED CAGE: SEBUAH TINJAUAN KRITIS ATAS DAMPAK TOXIC PRODUCTIVITY TERHADAP KESEHATAN MENTAL DAN KONSEP KESUKSESAN KARIER GENERASI MILENIAL-Z" - Fredlina, Sipta Firstina (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
This research examines the significant differences between success stories in the workplace and the reality of toxic productivity in a harsh work culture by critically reviewing academic literature. Using the metaphor of a "golden cage," this research demonstrates how seemingly bright career achievements can stifle one's mental health. This research uses a qualitative approach with literature analysis, searching for references related to a work culture that glorifies constant busyness with toxic productivity, making the sacrifice of mental health commonplace for the sake of recognition from others. The research findings indicate that current "success" often rests on a foundation of exhaustion, loss of personal freedom, and an identity solely defined by how much one can produce. This research synthesises various academic perspectives to reveal the mismatch between the glittering veneer of success (social recognition, financial rewards) and the confining cage (anxiety, alienation, loss of meaning in life). This research contributes to a critical understanding of the need for a more human and sustainable redefinition of career success.